Hypothetical structure of interaction of factors that determine situation-related efficacy and actual player and team quality - Trninic, S.; Papic, V.; Trninic, M. (Acta Kinesiologica, 2010)
We hereby suggest a hypothetical structure of interaction of factors with different mutual connections and relations that determine situational efficacy and actual player and team quality. The model is based on arguments provided by scientific research and expert knowledge and experience based on exteriorly depictive factors with direct and/or implicit influence on players' situational efficacy. On the other hand, there are some factors mentioned that reciprocally influence player and game actual quality (sports form level, game organisation level, training process and coach's leadership behaviour, integral player and whole team preparation). In fact, the most significant features of sports games are incorporated in very complex functional and interactional relations, and so the analysis of individual variables cannot provide with a complete insight on the structure and the dynamics of team sports. Here presented are complex interconnections and dynamic interactions amongst the factors that determine situational efficacy which is the indicator of actual game and player quality. It is assumed that the assessment of consistency or variability of situational athlete efficacy based on a sequence of games, as well as the assessment of potential and overall actual player quality is not just the basis for player selection and team formation, sports preparation planning and programming and game management, but also a precondition for determining the course of development of individual players and teams in the sports preparation system. That is a valuable source of information that helps experts to construct, supervise, correct and conduct sports preparation, and to organise and carry out individual, group or team training. In fact, the research on situational player and team efficacy as a whole, based on statistic records where only final offence and defence actions are registered, is not precise enough because it does not encompass contents and/or events in the game that proceed successful and unsuccessful final actions of the players nor the teams. It is therefore necessary to set up a system that links the subjective and the objective assessment of player and whole team quality.